Analisis Kemampuan Berpikir Historis pada Peserta Didik Kelas XI SMAN 2 Selimbau Kabupaten Kapuas Hulu : Penelitian - Yoppi Dwi Saputra; Ika Rahmatika Chalimi; Haris Firmansyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to identify the analysis of Historical Thinking Skills in Students in History Learning of Class XI SMAN 2 Selimbau, Kapuas Hulu Regency, where the researcher has conducted this research as one of the final assignments. The research method used is to collect descriptive qualitative data through observation, interviews, and documentation. The results of the data obtained in this study, the researcher found similarities between social studies and science students in historical thinking, because the teacher only used the discussion method in class. Data collection was carried out by interviewing informants such as the Principal, History Teacher, Deputy Curriculum, BK Teacher and also students. In addition, the researcher also used documentation sources in the form of photos, documents, and school archives. The results of the study obtained by the researcher showed that: (1) Analysis of Historical Thinking Skills of Students in the implementation of history learning in class XI social studies and science SMAN 2 Selimbau, Kapuas Hulu Regency, students are quite good at learning history, their activity in class as usual, some are active and some are not. (2) The constraints may be limited historical sources, lack of interest in studying history and lack of creativity of teachers when teaching. (3) The solution may be to improve knowledge, seek more information outside of school and not be fixated on books. That way, it can increase the insight of the students themselves.